Retrieval Practice and Distributed Practice: The Case of French Canadian Students. (June 2019) - Gagnon, Mathieu; Cormier, Stéphanie
Much evidence suggests that long-term retention can be maximized by practicing the recall of information and spreading out one's learning over time. Nevertheless, previous surveys have shown that undergraduates often ignore the benefits of such strategies and engage in less efficient techniques such as repetitive reading and massed studying. To date, however, this research has focused exclusively on Americans and has paid little attention to potential gender differences. The present study addressed such limits by using a web-based survey of the rereading, self-testing, and distributed learning habits of 1, 371 French-speaking Canadian undergraduates. Overall, the results are consistent with American data, suggesting that their original observations extend beyond American campuses. Furthermore, chi-square tests followed by standardized residual analyses suggest that females are more likely to engage in distributed learning than their male counterparts. On the contrary, there was little evidence of such an advantage in the context of self-testing.